Does Cannabis Extract Obtained From Cannabis Flowers With Maximum Allowed Residual Level of Aflatoxins and Ochratoxin a Have an Impact on Human Safety and Health? - Serafimovska, Tijana; Stefanovski, Sasho; Erler, Joachim; Keskovski, Zlatko; Stefkov, Gjoshe; Mitevska, Marija; Darkovska Serafimovska, Marija; Balkanov, Trajan; Tonic Ribarska, Jasmina (Frontiers in Medicine, 2021)
Aim: The aim of this study was to investigate whether the cannabis extract obtained from cannabis flowers that contain the maximum allowed level of mycotoxins affects human safety and health. For that purpose, a novel liquid chromatography with tandem mass spectrometry (LC/MS/MS) method was developed and validated for the determination of aflatoxins and ochratoxin A (OchA) in cannabis extracts to demonstrate that this analytical method is suitable for the intended experimental design. Methods: Experimental design was done by adding maximum allowed concentration of aflatoxins (B1, B2, G1, G2) and OchA according to the European Pharmacopeia related to cannabis flowers. The concentration of aflatoxins and OchA was determined using the same LC/MS/MS analytical method in the starting material (dry flower) before preparing the spiked sample and after obtaining decarboxylated extract with ethanol 96%. Results: The results obtained indicate that aflatoxins and OchA, primarily added to the cannabis dried flowers, were also determined into the obtained final extract in amounts much higher (m/m) than in the starting plant material. Conclusion: With this experiment, we have shown that mycotoxins, especially aflatoxins, which are extremely toxic secondary metabolites, can reach critical values in cannabis extracts obtained from dry cannabis flowers with the maximum allowed quantity of mycotoxins. This can pose a great risk to consumers and their health especially to those with compromised immune systems.